ASUHAN KEBIDANAN IBU HAMIL TRIMESTER I DENGAN EMESIS GRAVIDARUM PADA NY. S DI KLINIK SUNDARI KOTA CILEGON-BANTEN TAHUN 2019 - Lina Marliana (Journal Of Applied Health Research And Development, 2020)
One of the causes of physiological changes in pregnancy is emesis gravidarum, half of pregnant women experience nausea and vomiting, although the incidence is only about 0.5% to 2%. Gravidarum emesis is a natural symptom or often found in the first trimester of pregnancy. The purpose of this case study is to increase knowledge about midwifery care in first trimester pregnant women with emesis gravidarum using the varney management approach. This case study method is a qualitative case study, because it is done by interview and observation. Primary and secondary data types from interviews, history taking, direct observation, and register books and MCH books. After an assessment of midwifery care for pregnant women in Ny. S with emesis gravidarum, given Fe 1x1, calcium 1x1 and vitamin B complex, giving IEC includes giving IEC about signs of discomfort being complained of, giving IEC about nutrition of pregnant women, giving IIE about danger signs in pregnancy and encouraging repeat visits. It is expected for all pregnant women to carry out regular checks to monitor the condition of the mother and fetal development